Application of live video streaming over grid and cloud infrastructures - Karakasilis, Dimitris; Georgatos, Fotis; Lambrinos, Lambros (My University, 2011)
Video streaming is a very demanding application in its resources. We used a previously proposed architecture, to implement a solution that will use the GRID or a Cloud infrastructure to stream video. The goal was to create an application that will allocate resources dynamically and escalate in a manner corresponding to the demand. We developed and tested the application as a proof of concept and created a prototype implementation. This paper documents our experimental methodology and findings.
Keywords: Acoustic streaming; Information technology; Cloud computing